2022
DOI: 10.3389/fimmu.2022.842949
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-Derived Suppressor Cells in COVID-19: The Paradox of Good

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the causative agent of the ongoing coronavirus disease 2019 (COVID-19) pandemic. Viral replication in the respiratory tract induces the death of infected cells and the release of pathogen- associated molecular patterns (PAMPs). PAMPs give rise to local inflammation, increasing the secretion of pro- inflammatory cytokines and chemokines, which attract immune cells from the blood into the infected lung. In most individuals, lung-recruited cells clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 125 publications
2
20
0
Order By: Relevance
“…The inflammatory/suppressive signals in TME promote the recruitment and expansion of several type of immunosuppressive cells such as myeloid derived suppressor cells (MDSCs), tumor-associated macrophages (TAMs) or Treg responsible for the strong inhibition of the host immune response ( 27 29 ). A similar suppressor cell expansion as well the increase in the neutrophil/lymphocyte ratio that characterize cancer patients ( 30 ) was also observed during viral emerging infection such as COVID-19 ( 31 , 32 ). Their effects in dampening both antiviral and antitumoral immunity can therefore be exacerbated in cancer patients experiencing emerging infections.…”
Section: The Immune Response In Ic Patients: a Complex Scenariosupporting
confidence: 57%
“…The inflammatory/suppressive signals in TME promote the recruitment and expansion of several type of immunosuppressive cells such as myeloid derived suppressor cells (MDSCs), tumor-associated macrophages (TAMs) or Treg responsible for the strong inhibition of the host immune response ( 27 29 ). A similar suppressor cell expansion as well the increase in the neutrophil/lymphocyte ratio that characterize cancer patients ( 30 ) was also observed during viral emerging infection such as COVID-19 ( 31 , 32 ). Their effects in dampening both antiviral and antitumoral immunity can therefore be exacerbated in cancer patients experiencing emerging infections.…”
Section: The Immune Response In Ic Patients: a Complex Scenariosupporting
confidence: 57%
“…Another crucial issue in the pathogenesis and vaccination of COVID-19, which is related to CCL2, is the increase in the frequency of monocytic myeloid-derived suppressor cells (M−MDSCs) and the recruitment of these cells, which disrupt the host’s antiviral responses in a chronic inflammation condition. On the other hand, how MDSCs influence immunization following COVID-19 vaccination remains to be determined [138] . An investigation reported that the number of M−MDSCs was significantly higher in the blood of patients with severe COVID-19 than in control subjects.…”
Section: The Ccl2/ccr2 Axis In Covid-19mentioning
confidence: 99%
“…Increased levels of Arg-1 and ROS can further be observed in AP patients, especially those with a severe clinical course [ 174 ]. Similarly, expansion of M-MDSCs was reported together with increased Arg-1 activity in plasma, and these are associated with severity and fatal outcome in COVID-19 patients [ 175 ].…”
Section: The Role Of Mhla-dr In Ap and Covid-19mentioning
confidence: 99%
“…A proportion of circulating HLA-DR −/low monocytes seen in both AP and COVID-19 patients have been identified as CD14 + CD11b + HLA-DR −/low CD15 − monocytic myeloid-derived suppressor cells (M-MDSCs); these cell types may cloud earlier studies on the topic, as they could be misidentified as HLA-DR −/low classical monocytes [ 174 , 175 , 176 ]. M-MDSCs are characterized by their potent immunosuppressive effects on other immune cells, especially T cells, through various mechanisms including secretion of arginase-1 (Arg-1), and inducible nitric oxide synthase, production of reactive oxygen and nitrogen species, secretion of cytokines including TGF-β and IL-10, and induction of regulatory T cells [ 175 ].…”
Section: The Role Of Mhla-dr In Ap and Covid-19mentioning
confidence: 99%